Children prefer to learn from mind‐readers. (28th April 2014) - Kim, Sunae; Harris, Paul L.
<x xml:space="preserve">Abstract</x> Kim and Harris (2014, J. Cogn. Dev.) showed that children selectively learned from an informant who produced apparently magical outcomes as compared to another informant who produced only ordinary outcomes in the domain of everyday physics. In the present study, we tested children's ability to differentiate between and selectively learn from informants who displayed either an extraordinary or an ordinary ability in the domain of everyday psychology. Prior studies have shown that children come to appreciate what is ordinarily involved in knowing the private mental states of other people. Drawing on this research, we asked whether 3‐ to 4‐ and 5‐ to 6‐year‐old children preferentially learned from an informant who knew another person's mind via either an ordinary or an extraordinary form of communication. As compared to younger children, older children were more likely to learn from the extraordinary informant. Moreover, children's ability to differentiate between the two informants was a better predictor of their learning from the extraordinary informant than age. We discuss the findings in the light of prior work on selective learning, children's ideas about prayer and their understanding of impossibility.